EFFECT OF INULIN EXTRACT FROM DAHLIA TUBER (dahlia variabilis) ON CORONARY ARTERY HISTOPATHOLOGY IN RATS WITH TYPE 2 DIABETES MELLITUS (DM) - Hopi, Zikrilla mayuli; Ismawati, Ismawati; Saryono, Saryono; Romus, Ilhami; Putri, Veni Dayu; Yanti, Sri; Dyna, Fitri (Biomedika, 2025)
Atherosclerosis in diabetes mellitus (DM) patients is prevented by using inulin to increase glucose metabolism and reduce cholesterol synthesis. Therefore, this research aimed to analyze dahlia tuber inulin extract to determine the effect on coronary artery histopathology in type 2 DM rats. A total of 20 male Wistar rats were divided into five groups, namely negative control without treatment, DM, DM + 0.5 mg/gBW/day inulin extract, DM + 1 mg/gBW/day inulin extract, and DM + 1.5 mg/gBW/day inulin extract. Furthermore, DM induction was carried out by administering 60 mg/kgBB streptozotocin and 120 mg/kgBB nicotinamide. The results of coronary artery histopathology readings showed that the highest and lowest scores of atherosclerosis were in Groups II (0,91±0,17) and V (0,08±0,1), respectively. Data analysis using Kruskal Wallis test reported significant results (p<0.05), while Mann-Whitney test showed differences between control and DM, DM, and inulin groups (III, IV, V). In this context, the administration of dahlia tuber inulin extract to rats induced by Type 2 DM prevented atherosclerosis in histopathological image of coronary artery.